The effect of dust particles on cellulose degradation. (3rd July 2016) - Bartl, Benjamin; Mašková, Ludmila; Paulusová, Hana; Smolík, Jiří; Bartlová, Lenka; Vodička, Petr
Abstract : This study focuses on the changes in properties of cellulose-based paper, which can take place as a consequence of its contamination by dust particles. The PM1 (fine) and PM10 (coarse) fractions of the dust particles from archival repositories were collected on cellulose filters Whatman 41, polytetrafluorethylene, and quartz filters. The latter two types of samples were subsequently analyzed gravimetrically, with ion chromatography, PIXE, and the thermal–optical transmission method, giving mass, ionic, elemental carbon, and organic carbon concentrations. After artificial aging, the viscosity-average degree of polymerization of cellulose (DPv ) was measured. It was confirmed that cellulose-based paper can undergo substantial changes when contaminated by dust particles and artificially aged. The decrease of the DPv of cellulose showed a negative correlation with the deposited mass of sulfate ions in the dust particles. Considering the particle size fraction, the results suggest the decisive importance of the fine (PM1) particles. The results provide better understanding of how particulate matter contributes to the chemical degradation of cellulose-based paper. Such knowledge is of importance when considering appropriate conservation measures in archives, libraries, and galleries.